Implementation via vote delegation - Correa-Lopera, Guadalupe (My University, 2019)
For some years now, the number of political parties asking for the direct participation of citizens in the decision making process is increasing. These parties defend that citizens should be able to decide on each and every one of the issues that comes up for discussion, being thus what the majority of people desires for such specific issue carried out. However, organizing a referendum on each single issue may involve serious problems. An alternative option is to allow voters to delegate the decision making process to a politician who, once in power, will decide on each single issue. We wonder under which conditions the two aforementioned procedures to make decisions may be equivalent in terms of the developed policies for each of the considered issues.
Keywords: Democracia directa; Direct democracy; Representative democracy